2005
DOI: 10.1192/pb.29.12.452
|View full text |Cite
|
Sign up to set email alerts
|

New long-stay patients in a psychiatric admission ward setting

Abstract: Aims and MethodThis is a descriptive study of the admissions of new long-stay patients and their outcome in a district with minimal access to longer-stay in-patient beds. Cases were identified through an ongoing in-patient census and information was gathered by retrospective case-note review.ResultsThirty-nine new long-stay admissions were identified. High rates of living alone, early readmission following previous discharge and use of the Mental Health Act 1983 were noted. The 39 admissions occupied 12% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(9 reference statements)
0
7
1
Order By: Relevance
“…This was less than figures obtained from previous studies i.e. 12% in a British study by Cowan and Walker (2005) 22 and 11% from a local study in Calabar, Nigeria. 6 However, this 10.7% bed occupancy by the long stay patients in our study remains quite high placing a heavy burden and pressure on the hospital facilities, especially with the current increasing number of acutely ill patients being brought to the centre on a daily basis that require hospitalization.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This was less than figures obtained from previous studies i.e. 12% in a British study by Cowan and Walker (2005) 22 and 11% from a local study in Calabar, Nigeria. 6 However, this 10.7% bed occupancy by the long stay patients in our study remains quite high placing a heavy burden and pressure on the hospital facilities, especially with the current increasing number of acutely ill patients being brought to the centre on a daily basis that require hospitalization.…”
Section: Discussioncontrasting
confidence: 54%
“…17,22 The possible explanation in our study could be that male psychotic patients are more difficult to manage in the community hence increasing the likelihood of abandonment 14 and 43.1 years in the Calabar, Nigerian study. 6 The mean length of stay in the study was 11.4+15.0 years (range of 0.5-57 years).…”
Section: Discussionmentioning
confidence: 90%
“…32,33 In such cases, collaboration between all relevant in-and outpatient services is crucial in facilitating the discharge process.…”
Section: 173031mentioning
confidence: 99%
“…New long stay patients continue to accrue, despite the movement towards community based care [ 4 ]. A study by Cowan and Walker [ 28 ] found that a small number of long-stay admissions took up 12% of available admission ward capacity over 3 years, placing demands on the inpatient service greatly disproportionate to their numbers. Similarly it has been shown that many patients in acute admission units are inappropriately placed new long stay patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%